Green Product dan Keputusan Pembelian Konsumen Muda - Dianti, Nia Resti; Paramita, Eristia Lidia (Fakultas Ekonomi Universitas Samudra, 2021)
The purpose of this study is to determine whether there is an effect between green product made by the company on the decision to buy green products among young consumers in Indonesia, using green product identification as a moderating variable. This study uses multiple linear regression analysis (MRA) techniques. Data were obtained through questionnaires to 200 young consumers. The results of this study indicate that green products have a significant and positive direct influence on the purchasing decisions of young consumers. However, when green product identification is included as the moderating variable, the indirect relationship pattern between green products has a positive but insignificant effect on the purchasing decisions of young consumers. Thus, it is concluded that the decision of young consumers to buy green products is actually determined by the awareness of the importance of green products, not green product identification.